The effect of liver enzymes on adiposity: a Mendelian randomization study. - Liu J; Au Yeung SL; Kwok MK; Leung JYY; Lin SL; Hui LL; Leung GM; Schooling CM (Springer Nature Limited, 2019)
Poorer liver function is positively associated with diabetes in Mendelian randomization (MR) studies. Observationally, adiposity is associated with poorer liver function. To clarify the etiology, we assessed the association of liver enzymes with adiposity observationally and using two-sample MR for validation. In the "Children of 1997" birth cohort, we used multivariable linear regression to assess the associations of alanine transaminase (ALT) and alkaline phosphatase (ALP) at ~17.5 years with body mass index (BMI) (n = 3,458). Using MR, genetic predictors of ALT, ALP and gamma glutamyltransferase (GGT), were applied to genome-wide association studies of BMI (n = 681,275), waist circumference (WC) (n = 224,459) and waist-hip ratio (WHR) (n = 224,459) to obtain unconfounded estimates. Observationally, ALT was positively associated with BMI (0.10 kg/m2 per IU/L, 95% confidence interval (CI) 0.09 to 0.11). ALP was inversely associated with BMI (-0.018 kg/m2 per IU/L, 95% CI -0.024 to -0.012). Using MR, ALT was inversely associated with BMI (-0.14 standard deviation per 100% change in concentration, 95% CI -0.20 to -0.07), but not WC or WHR. ALP and GGT were unrelated to adiposity. Poorer liver function might not cause adiposity; instead higher ALT might reduce BMI, raising the question as to the role of ALT in body composition.
Keywords: Adiposity; Adolescent; Alanine Transaminase; Alkaline Phosphatase; Body Mass Index; Female; Genome-Wide Association Study; Humans; Linear Models; Liver; Male; Mendelian Randomization Analysis; Polymorphism, Single Nucleotide; gamma-Glutamyltransferase